Dampak Komersialisasi Kekayaan Intelektual Komunal Terhadap Kesejahteraan Masyarakat Adat - Alfa Rizky Voth; Turshe Pramesta Syah; Eric Andhika Widyadhana (CV. ITTC INDONESIA, 2025)
Commercialization of communal intellectual property (CIK) has become a strategic issue in the protection of indigenous peoples' rights in the era of creative economy and globalization. KIK includes traditional cultural expressions, traditional knowledge, and genetic resources that are passed down from generation to generation and attached to the collective identity of indigenous peoples. This research aims to analyze the impact of KIK commercialization on the welfare of indigenous peoples from a legal, economic and social perspective. Using a normative juridical approach and case studies in several indigenous communities in Indonesia, this article examines how commercialization practices whether carried out by outsiders or by indigenous peoples themselves can provide economic benefits, but also present the potential for exploitation, marginalization and inequality in benefit distribution. It is found that the success of commercialization is highly dependent on adequate legal recognition and protection of indigenous peoples' collective rights and their active involvement in the process of KIK management and utilization. Therefore, the strengthening of collective rights-based legal protection systems and fair revenue sharing mechanisms are key requirements to ensure that the commercialization of KIK truly contributes to improving the welfare of indigenous peoples, without compromising inherent cultural values and local wisdom.